An infrared spectral database for gas-phase quantitation of volatile per- and polyfluoroalkyl substances (PFAS). (January 2023) - Baker, Tracy J.; Tonkyn, Russell G.; Thompson, Christopher J.; Dunlap, Megan K.; Koster van Groos, Paul G.; Thakur, Nikita A.; Wilhelm, Michael J.; Myers, Tanya L.; Johnson, Timothy J.
Highlights: Poly- and per-fluoroalkyl substances are known and persistent environmental hazards. Database of quantitative gas-phase infrared spectra of perfluoroalkyl substances. Data demonstrated to detect PFAS thermal degradation compounds. Validated / documented methods for reliable data for remote and in situ sensing. Abstract: We report the construction of a database of quantitative infrared spectra specifically targeting volatile fluorocarbon gases that may be emitted during thermal treatment of per- and polyfluoroalkyl substances (PFAS) to assist understanding of treatment processes and improve quantification. To populate this database, protocols derived from the Pacific Northwest National Laboratory infrared spectral database have been employed. Each spectrum in the database is a weighted average derived from 10 or more individual measurements at different partial pressures (static method) or flow rates (dissemination method) to yield good fidelity for both strong and weak infrared signatures, with each composite spectrum ranging from ≥ 6500 cm −1 to ≤ 600 cm −1 at an apodized resolution of 0.112 cm −1 . This resolution was chosen to fully resolve all spectral features, recognizing that atmospheric pressure broadening results in nearly all ro-vibrational lines having linewidths ≥ 0.1 cm −1 . As an example case, application of the database is demonstrated via identification and quantification of dominant 1H-perfluoroheptane and perfluorohept-1-ene fluorocarbon products resulting from thermal decomposition of perfluorooctanoate (PFOA) below 450 °C.